Essentials of oceanography - Garrison, Tom 1942- (Cengage Learning, 2015)
Provides students with an understanding of the scientific questions, complexities, and uncertainties involved in ocean use, and the role and importance of oceans in nurturing and sustaining life on the planet. This book illustrates the interdisciplinary nature of marine science, allowing students to see its links to biology, chemistry, and more